Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0141
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in the Construction Industry: a Rapid Review

Abstract: Principles of lean construction have been suggested as strategies towards improving health and safety (H&S) in construction. Previous research has typically focused on the physical aspects of H&S; yet individuals who work within the construction industry have an increased risk of suffering from mental health conditions. This is an area which is gaining attention but is yet to be researched in depth. Through a rapid review of literature, this paper identifies 15 studies, and reviews the current literature conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…A systematic review identified high work demands (such as long hours) and lack of job control (e.g., few opportunities for decision-making and opportunities to speak about work issues) as the primary stressors for construction workers [ 26 , 27 ]. According to a meta-analysis, role conflict (incompatible work tasks or expectations), role ambiguity (lack of clarity or uncertainty about job responsibilities), job insecurity, interpersonal conflict (disagreement or frictions) and role overload (excessive workload, long hours, time pressure) were the stress factors which showed the strongest pooled associations with work-related distress and burnout [ 29 ]. In an industry that relies heavily on the timely flow of information and efficient communication between different collaborators of a project, poor communication and information sharing were deemed to be fundamental psychosocial risks [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review identified high work demands (such as long hours) and lack of job control (e.g., few opportunities for decision-making and opportunities to speak about work issues) as the primary stressors for construction workers [ 26 , 27 ]. According to a meta-analysis, role conflict (incompatible work tasks or expectations), role ambiguity (lack of clarity or uncertainty about job responsibilities), job insecurity, interpersonal conflict (disagreement or frictions) and role overload (excessive workload, long hours, time pressure) were the stress factors which showed the strongest pooled associations with work-related distress and burnout [ 29 ]. In an industry that relies heavily on the timely flow of information and efficient communication between different collaborators of a project, poor communication and information sharing were deemed to be fundamental psychosocial risks [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…People working in construction are particularly vulnerable to suffering from mental health issues (Oswald et al, 2019). There are various systemic and inherited problems in construction (Sarhan et al, 2017), such as its risk-averse and blaming culture, cut-throat price competition, the traditional macho culture, long and fragmented supply chains, late payments, slim profit margins, tight deadlines and challenging working conditions, skills shortage and job insecurities, all of which contribute towards increasing stress and anxiety in construction.…”
Section: Why Are People In Construction Particularly At Risk?mentioning
confidence: 99%
“…Many research studies have focused on investigating physical health problems and safety performance in construction. However, much less research has studied mental health issues affecting construction practitioners (Oswald et al, 2019). In addition, efforts in both academic and practitioner communities in construction focus mainly on managing occupational stress, as opposed to preventing or reducing its occurrence.…”
Section: Research Gap and Objectivesmentioning
confidence: 99%
“…A systematic review identified high work demands (such as long hours) and lack of job control (e.g., few opportunities for decisionmaking and opportunities to speak about work issues) as the primary stressors for construction workers [26,27]. According to a meta-analysis, role conflict (incompatible work tasks or expectations), role ambiguity (lack of clarity or uncertainty about job responsibilities), job insecurity, interpersonal conflict (disagreement or frictions) and role overload (excessive workload, long hours, time pressure) were the stress factors which showed the strongest pooled associations with work-related distress and burnout [29]. In an industry that relies heavily on the timely flow of information and efficient communication between different collaborators of a project, poor communication and information sharing were deemed to be fundamental psychosocial risks [30].…”
Section: The Psychosocial Work Environment In the Construction Sectormentioning
confidence: 99%